Ophiostomatoid fungi associated with Ips subelongatus, including eight new species from northeastern China - Zheng Wang; Ya Liu; Huimin Wang; Xianjing Meng; Xuewei Liu; Cony Decock; Xingyao Zhang; Quan Lu (IMA Fungus)
Abstract Ips subelongatus is a major pest that infects larch plantations over large areas of northern and northeastern China. Ips species are closely associated with ophiostomatoid fungi that are morphologically well-adapted for dispersal by beetles. These associations result in important threat for coniferous forests worldwide. The aim of this study was to characterize the ophiostomatoid communities associated with I. subelongatus infesting Larix species and sympatric Pinus sylvestris var. mongolica in northeastern China forests. Morphological and multilocus phylogenetic approaches (based on six markers: ITS, LSU, 60S, β-tubulin, EF-1α, and CAL gene regions) allowed identifying 14 species of four genera (Ceratocystiopsis, Endoconidiophora, Leptographium and Ophiostoma). Eight species are showed to be new to science. Most strains resided in two Ophiostoma species complexes, viz. the O. clavatum and the O. ips complexes, all together accounting for 76.8% of all isolates. Ophiostoma hongxingense sp. nov., O. peniculi sp. nov., and O. subelongati sp. nov. (O. clavatum complex) and O. pseudobicolor sp. nov. (O. ips complex) were the four dominant species. The ophiostomatoid communities associated with larch bark beetles, I. cembrae and I. subelongatus, in Europe and Asia, China and Japan, also were compared. These comparisons showed distinct, specific assemblage patterns.